KONSELING KELOMPOK DENGAN TEKNIK BIBLIOTERAPI UNTUK MENGURANGI KECANDUAN GAME ONLINE PADA ANAK: SEBUAH KAJIAN LITERATUR [GROUP COUNSELING WITH BIBLIOTHERAPY TECHNIQUES TO REDUCE ONLINE GAME ADDICTION IN CHILDREN: A LITERATURE REVIEW] - Muhammad Rizai (Journal of Contemporary Islamic Counselling, 2021)
This study was conducted with the aim of describing the stages of group counseling with bibliotherapy techniques as an effort to reduce online game addiction behavior in children. The method of data collection is done by conducting a literature study on scientific journals and books that are relevant to the research topic. The result is that there are 4 stages in conducting group counseling with bibliotherapy techniques, namely the formation stage, the transition stage, the activity implementation stage and the termination stage. The bibliotherapy technique is used at the implementation stage of the activity.